Factors affecting velvet antler weights in free-ranging reindeer in Alaska - Prichard, Alexander K.; Finstad, Greg L.; Shain, Drew H. (Rangifer, 1999)
Free-ranging reindeer on the Seward Peninsula in western Alaska are rounded up from late May to early July and antlers are removed. We used data collected from 1987 to 1997 to determine how velvet antler weights of males and females varied with age, year, reproductive status, Julian date, and body weight. Male antler weights increased with age up to age five years, and were lower in castrates than in bulls. There was a significant positive relationship between body weight and antler weight in both sexes. Female antler weights increased with age until at least age nine. Lactating females had lower antler weights than non-lactating females, but this effect is better explained by differences in body weight. Antler weight of individual reindeer at age two years was better predicted by their antler weights as yearlings than their body weight as yearlings.